Relationships between interleukin-12B and interleukin-10 gene polymorphisms and hepatitis C in Chinese Han hemodialysis patients. (23rd January 2015) - Zhu, Bei; Wang, Cuiyu; Zhang, Xiaoli; He, Juan; Wu, Jianqing; Yu, Rongbin; Zhao, Weihong
Abstract: Background and Aims : Hepatitis C virus (HCV) commonly causes a chronic infection but portion of hemodialysis patients are able to resistant to HCV infection, even clear the virus naturally. Interleukin-10 (IL-10) and interleukin-12 (IL-12) are crucial regulators of the immune response to T-helper 1 (Th1) or T-helper 2 (Th2) categories and play a role in autoimmune and infectious diseases. This study was undertaken to investigate the possible association of genetic polymorphisms of 3′ untranslated region (3′UTR) of the IL-12B (−1188) and IL-10 (−592 and −819) and hepatitis C in Chinese Han hemodialysis (HD) patients. Methods : The genotyping of IL-12B 3′UTR and IL-10 −592 and −819 were performed by polymerase chain reaction (PCR) restriction fragment length polymorphism (RFLP) method. Results : Compared with the IL-12B-AA genotype, CC and combined CC/AC genotypes were associated with a significant decreased risk of HCV infection in Chinese hemodialysis patients ( p < 0.001). However, the IL-10−592 and −819 genotypes were not found significant difference both between the anti-HCV (+) and anti-HCV (−) patients ( p > 0.05) and the persistent infection and viral clearance HD patients ( p > 0.05). Conclusions : The present study indicated that the polymorphisms of IL-12B 3′UTR might contribute to the susceptibility of HCV infection in Chinese HD population.